EEG in genetic generalized epilepsies - V. Yu. Nogovitsyn; A. A. Sharkov (Эпилепсия и пароксизмальные состояния, 2020)
Genetic, or idiopathic, generalized epilepsies (GGEs or IGEs) includes childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy (JME), and epilepsy with generalized tonic-clonic seizures alone (GTCS-a).Aim. to characterize the capabilities of electroencephalography (EEG) for the diagnosis of various forms of genetic generalized epilepsyMaterials and methods. Literature data in Pubmed, Google Scholar was analyzed. In addition, own observations and clinical cases were systematized.Results. The article presents the data of morphology and topography of spike-wave discharges, as well as other patterns of EEG in the GGE – poly-spike activity, photoparoxysmal response, occipital intermittent rhythmic delta activity (OIRDA), fixation-off sensitivity and generalized paroxysmal fast activity (GPFA), as well as epileptiform K-complexes, the allocation of which in an independent pattern is questioned by a number of neurophysiologists. The differences between interictal and ictal activity in the GGE are discussed in detail; electroencephalogram (EEG) informativity modifiers are considered. The morphology of atypical features in the GGE is considered. The role of EEG in the differential diagnosis of CAE, JAE, JME, GTCS alone with the description of typical, atypical features, study scenarios and diagnostic criteria for each form are considered.Conclusions. Typical EEG features of GGE significantly simplify the differential diagnosis of electroclinical syndromes. There are “non-classical” features of EEG in the GGE, which do not contradict the diagnosis. To reveal the peculiarities of epileptiform discharges distribution, video EEG monitoring with night-time sleep and the use of several modality stimuli is preferable. Incorrect interpretation of EEG is dangerous for the patient.